2011
DOI: 10.2165/11591600-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib Monotherapy for the Maintenance Treatment of Non-Small Cell Lung Cancer after Previous Platinum-Containing Chemotherapy

Abstract: The UK National Institute for Health and Clinical Excellence (NICE) invited the manufacturer of erlotinib (Roche) to submit evidence for the clinical and cost effectiveness of erlotinib as monotherapy for the maintenance treatment of patients with non-small cell lung cancer (NSCLC) and stable disease following previous treatment with four cycles of platinum-containing therapy. The Liverpool Reviews and Implementation Group (LRiG) at the University of Liverpool was commissioned to act as the Evidence Review Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 11 publications
(12 reference statements)
0
10
0
3
Order By: Relevance
“…Three studies have indirectly compared direct medical costs between maintenance with pemetrexed and maintenance with another drug (Table 8). 20,27,28 A US study showed that pemetrexed maintenance is more cost-effective for patients with non-squamous NSCLC than erlotinib, because the ICER for pemetrexed versus erlotinib (US $150,260/LYG) is within the acceptable range of willingness to pay 20. Another UK study also showed a clear advantage in favor of pemetrexed, ICER for erlotinib versus pemetrexed, £84,029/QALY gained 27.…”
Section: Cost-effectiveness Of Pemetrexed Maintenance Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies have indirectly compared direct medical costs between maintenance with pemetrexed and maintenance with another drug (Table 8). 20,27,28 A US study showed that pemetrexed maintenance is more cost-effective for patients with non-squamous NSCLC than erlotinib, because the ICER for pemetrexed versus erlotinib (US $150,260/LYG) is within the acceptable range of willingness to pay 20. Another UK study also showed a clear advantage in favor of pemetrexed, ICER for erlotinib versus pemetrexed, £84,029/QALY gained 27.…”
Section: Cost-effectiveness Of Pemetrexed Maintenance Therapymentioning
confidence: 99%
“…20,27,28 A US study showed that pemetrexed maintenance is more cost-effective for patients with non-squamous NSCLC than erlotinib, because the ICER for pemetrexed versus erlotinib (US $150,260/LYG) is within the acceptable range of willingness to pay 20. Another UK study also showed a clear advantage in favor of pemetrexed, ICER for erlotinib versus pemetrexed, £84,029/QALY gained 27. In contrast, a European cross-market cost comparison showed that total monthly treatment costs per patient, including acquisition costs, administration costs, and costs of treating adverse events, were more reasonable for erlotinib than for pemetrexed, ie, €2,140 for erlotinib versus €3,453 for pemetrexed in France, €2,732 versus €5,534 in Germany, €1,518 versus €2,921 in Italy, and €2,048 versus €3,164 in Spain 28.…”
Section: Cost-effectiveness Of Pemetrexed Maintenance Therapymentioning
confidence: 99%
“…[34] Dickson et al, reported a statistically significant increase in both PFS and OS in patients with stable disease receiving switch maintenance with erlotinib compared with placebo for the maintenance treatment of NSCLC after previous platinum-containing chemotherapy. [35] A Phase II study of sequential erlotinib and chemotherapy as firstline treatment for advanced NSCLC by Mok et al, also showed sequential administration of erlotinib following gemcitabine/platinum chemotherapy led to a significant improvement in PFS. [36] Similarly, Coudert et al, showed that patients with advanced NSCLC following firstline platinum-based doublet chemotherapy derive a significant OS benefit from maintenance erlotinib therapy.…”
Section: Egfr Mutation Profilementioning
confidence: 99%
“…When the manufacturer submitted the dossier to NICE, the UK agency redid the calculations and found that erlotinib was not cost-effective for the British health care system 28. The NICE values were approximately £ 50,000 per QALY.…”
Section: Resultsmentioning
confidence: 99%